New venture strategic posture, structure, and performance: An industry life cycle analysis - Covin, Jeffrey G.; Slevin, Dennis P. (Journal of Business Venturing, 1990)
This paper describes a study of the strategic postures, structural forms, and performance levels of new ventures in three different industry settings—emerging, growing, and mature industries. Strategic posture was conceptualized as a firm's placement along the conservative-entrepreneurial continuum. Structural form was conceptualized as a firm's placement along the organic-mechanistic continuum. Managers' ratings on several financial performance criteria were used to assess new venture performance. Four hypotheses were tested in this study: H1 Strategic posture varies among new ventures in different industry life cycle stages. New ventures in emerging industries have the most entrepreneurial strategic postures. H2 The correlation between a firm's strategic posture score (i.e., its entrepreneurship level) and its performance is significantly more positive for new ventures in emerging industries than it is for new ventures in mature industries. H3 Organization structure varies among new ventures in different industry life cycle stages. New ventures in emerging industries have the most organic organization structures. H4 The correlation between a firm's organization structure score (i.e., its organicity level) and its performance is significantly more positive for new ventures in emerging industries than it is for new ventures in mature industries. Data were collected from the senior executives in 90 new ventures. These ventures were classified as existing in either emerging industries (n = 26), growing industries (n = 25), or mature industries (n = 39) according to their scores on a product/industry life cycle measure. Discriminant and correlation analyses were used to test the hypotheses. Consistent with hypotheses 1 and 3, results indicate that strategic posture and organization structure vary significantly over the industry life cycle and that new ventures in emerging industries have both the most entrepreneurial strategic postures and the most organic organization structures. Furthermore, the industry life cycle was found to moderate the strength of the relationship between new venture performance and both strategic posture and organization structure. Consistent with hypotheses 2 and 4, the correlations between a firm's performance and its strategic posture and organicity scores were significantly more positive among new ventures in emerging industries than among new ventures in mature industries. These results suggest that new venture performance is influenced by the fit between strategic posture, organization structure, and industry life cycle stage. Entrepreneurial strategic postures and organic organization structures appear to be most effective for new ventures in emerging industries and, accordingly, should be seriously considered by managers operating in these settings. High performance in growing industries is also generally associated with organic structural forms; however, the efficacy of entrepreneurial behaviors is appreciably less than in emerging industries. Managers in growing industries should create organic organization structures but be more cautious in adopting entrepreneurial strategic postures. Mature industries call for more mechanistic structures, and structural attributes designed to promote operating efficiency (e.g., standardization of operations, formal control mechanisms) are suggested for effective management. Entrepreneurial behaviors do not appear to be strongly related to new venture performance in mature industries, although individual cases and situations may vary.